Therapeutic effect of intraductal saline irrigation in chronic obstructive sialadenitis - Jo-Eun Kim; Sam-Sun Lee; Chena Lee; Kyung-Hoe Huh; Won-Jin Yi; Min-Suk Heo; Soon-Chul Choi (BMC, 2020)
Abstract Background The aim of the present study was to evaluate the effectiveness of intraductal irrigation using normal saline in chronic obstructive sialadenitis. Methods Patients who had one of the following symptoms were recruited: pain, swelling, stiffness, and dry mouth. A total of 58 salivary glands in 33 patients were diagnosed as having sialadenitis using sialography and ultrasonography. The patients were divided into two groups (swelling group and dry mouth group), according to the major complaint. Repeated intraductal irrigation was performed on each gland. Difference of symptom severity evaluated using numerical rating scale (NRS), and ductal width measured using ultrasonography were compared between the two groups. Results The average NRS score was significantly decreased from 6.0 to 3.3 after 3-5 visits of intraductal irrigation (P < 0.05). The reduction in NRS was greater in the swelling group than in the dry mouth group, although the difference between the groups was not statistically significant. There was no change of ductal width before and after the irrigation. Conclusions Intraductal irrigation according to this study method using normal saline is a simple treatment for the patients with chronic obstructive sialadenitis. It provides a conservative treatment option reducing the subjective symptoms.